2014
DOI: 10.1021/ic5014945
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Doping on Transport Properties in Cu–Bi–Se-Based Thermoelectric Materials

Abstract: The thermoelectric properties of Zn-, In-, and I-doped Cu1.7Bi4.7Se8 pavonite homologues were investigated in the temperature range from 300 to 560 K. On the basis of the comprehensive structural analysis using Rietveld refinement of synchrotron radiation diffraction for Cu(x+y)Bi(5-y)Se8 compounds with the inherently disordered crystallographic sites, we demonstrate a doping strategy that provides a simultaneous control for enhanced electronic transport properties by the optimization of carrier concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…The crystal structure of Cu-Bi-S can be understood based on the frame structure of monoclinic Bi 5 S 8 with the addition of Cu in slab I as interstitial ions and substitutional Cu at the unfilled Bi sites in slab II as an analogue of the pavonite family. [32][33][34][35][36][37] The addition of Cu to the mother compound (Bi 5 S 8 ) does not alter the frame structure significantly, whereas the introduction of the Cu ion distorts the local atomic structure causing the rearrangement of neighbour Cu, Bi, and S sites as well as the fluctuations of their site occupancies. These crystallographic features were also found in Cu-Bi-Se pavonite relatives with a similar structure.…”
Section: Monoclinic Cu X+y Bi 5ày Smentioning
confidence: 99%
See 1 more Smart Citation
“…The crystal structure of Cu-Bi-S can be understood based on the frame structure of monoclinic Bi 5 S 8 with the addition of Cu in slab I as interstitial ions and substitutional Cu at the unfilled Bi sites in slab II as an analogue of the pavonite family. [32][33][34][35][36][37] The addition of Cu to the mother compound (Bi 5 S 8 ) does not alter the frame structure significantly, whereas the introduction of the Cu ion distorts the local atomic structure causing the rearrangement of neighbour Cu, Bi, and S sites as well as the fluctuations of their site occupancies. These crystallographic features were also found in Cu-Bi-Se pavonite relatives with a similar structure.…”
Section: Monoclinic Cu X+y Bi 5ày Smentioning
confidence: 99%
“…It has been widely accepted that exploring semiconducting materials with a complex structure and a small bandgap is a promising route to develop new materials with a high TE figure of merit, since a low k lat originates in the structural complexity 30,31 and the small bandgap signifies the possibility of large S. In the extent of finding new complex structured materials with low k, our efforts have been dedicated to the n-type semiconducting complex structured pavonite homologues Cu x+y Bi 5Ày Ch 8 (Ch = S or Se), which have been recently investigated as TE materials, with intrinsically low k lat (0.41-0.55 W m À1 K À1 at 300 K) derived from an inherently disordered structure and specific atomic configurations with the coexistence of the interstitial and substitutional Cu sites followed by the displacement of chalcogen atomic sites in a large unit cell. [32][33][34] Generally, tuning the electronic transport properties for maximizing PF together with thermal transports by suppression phonon propagation is performed by altering chemical composition, the introduction of guest atoms into the host matrix, and elemental doping in TE materials. However, the precise prediction of the changes in the electronic and thermal transport properties of complex structured materials associated with the structural modifications through doping and/or compositional variation is challenging due to the lack of awareness about the role of structural elements (such as atomic configuration, site occupancy, disorder, and distances between various crystallographic sites of constituent atoms) affecting the TE properties.…”
Section: Introductionmentioning
confidence: 99%
“…The ZT value is a key parameter to evaluate thermoelectric properties and can be described by the formula: ZT = (σ·S 2 ·T)/κ, where σ, S, and κ are electrical conductivity, Seebeck coefficient, and thermal conductivity, respectively. 10,11 Therefore, it is important to improve the electrical conductivity and Seebeck coefficient, as well as weaken the thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] In particular, the As x Se 1Àx glass system has exhibited a sharp extreme at the composition of As 40 Se 60 , corresponding to the average coordination Z = 2.4, for wide range of properties such as the density, Young's modulus, shear modulus, bulk modulus and Poisson's ratio. 14,15 At the same time, Bi-doped ChG can extend novel near infrared (NIR) emission to the broad wavelength. Various studies on Se-based ChG by introducing Bi showed a strong TE power effect due to presence of TE Bi 2 Se 3 crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies on Se-based ChG by introducing Bi showed a strong TE power effect due to presence of TE Bi 2 Se 3 crystals. 14,15 At the same time, Bi-doped ChG can extend novel near infrared (NIR) emission to the broad wavelength. 16 This was accordant to a general "phonon glass electron crystal" (PGEC) strategy which has been implemented to develop TE materials with higher dimensionless figure of merit (ZT).…”
Section: Introductionmentioning
confidence: 99%